Analisis Optimalisasi Kinerja Bidang Bendahara Penerimaan Pajak Kendaraan Bermotor pada Kantor Samsat UPT Medan Utara: ( Studi Kasus : Kantor Samsat Jalan Putri Hijau No. 14 Medan- 20111 ) - Wahyuni Syahfitri; Saparuddin Siregar (Universitas Muhammadiyah Enrekang, 2022)
As a source of regional income that plays an important role in the Regional Revenue and Expenditure Budget (APBD), the Motor Vehicle Tax is very interesting in its contribution to revenue in the regional treasury which can increase and uphold regional household budget revenues. Judginng from current technological developments, the Motor Vehicle Tax is very helpful for regional income because more and more people choose motorized vehicles as a means of daily transportation. In carrying out the obligation to pay motor vehicle taxes, taxpayers need clear administrative facilities and must comply with procedures for submitting and fulfilling these obligations.In this case, the SAMSAT office is the right means to provide practical experience and knowledge in the field which is directly related to the of research that the authors examine using qualitative methods with a case study approach. Data were collected by [articipatory observation, in-depth interviews, and documents.